Redesigning School-Family Partnerships in The Digital Era: A Study of Parental Preferences in Primary Education in Indonesia - Hardianto, Deni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study examines the transformation of school-family partnerships amid digitization and the changing role of parents, especially millennial parents, in education. This study investigates the preferences of parents of primary school pupils in Yogyakarta, Indonesia, about effective methods of school-family collaboration in the digital age. Data were collected from 334 parents across five districts/cities in Yogyakarta utilizing a quantitatively descriptive survey approach, employing a structured questionnaire evaluated by experts and based on Epstein’s framework and parental involvement theory. The test identified five primary dimensions of parental preferences: participation, communication, digital engagement, parenting demands, and relationship quality. The results indicate that 98.8% of parents encountered rigid school timetables, whereas 94.3% favored asynchronous digital communication methods, including message platforms and learning management systems. Furthermore, 87.5% appreciated polite, reciprocal engagement with educators, while 89.1% endorsed the incorporation of digital tools to enhance accessibility and facilitate real-time cooperation. Despite a robust desire to engage in their children's education, parents faced considerable obstacles, especially concerning professional obligations and inflexible school policies. This research advances the field by introducing a responsive, participatory blended approach designed for millennial parents' specific traits. The concept prioritizes adaptability, inclusiveness, and the strategic utilization of existing ICT infrastructure to facilitate significant engagement. The findings provide essential insights for policymakers and school leaders in formulating adaptive family involvement strategies that align with the contemporary reality and digital proficiency of today's families.